Fenomena Kejahatan Perdagangan Manusia - Hidayatullah, Hidayatullah; Melisa, Melisa (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The crime of trafficking in persons is a very serious global issue, because many actors are interrelated, both as countries of origin, as well as countries of destination as well as transit countries. Therefore, various efforts must be made in combating this crime of human trafficking and must also involve many parties including the government, law enforcement, civil society, media, migrant workers, as well as transit and destination countries. The obstacle faced by Indonesian law enforcement is due to the lack of reports from victims of this human trafficking crime because they are already in other countries. The purpose of this article is to analyze and describe the effectiveness of Law Number 21 of 2007 concerning Eradication of the Crime of Trafficking in Persons and the Effectiveness of Law Number 36 of 2009 concerning Health Regulating the Prohibition of Trafficking in Human Organs. The method used is descriptive qualitative. The results of this study (1) Implementation of Law no. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons is deemed ineffective if it does not involve many countries, because there is still a lot of human trafficking, especially women and children for the purpose of sexual exploitation as commercial sex workers and exploitation of pornography (2) Law Number 36 Year 2009 concerning Health, especially in Article 92 which mentions the Functionalization of Criminal Law Against Acts, namely "Everyone who deliberately trades organs or body tissues under any pretext as referred to in Article 64 paragraph (3) shall be punished with imprisonment for a maximum of 10 (ten) years. and a maximum fine of Rp. 1,000,000,000.00 (one billion rupiah)''.